2018
DOI: 10.1007/s10096-018-3406-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different human tissue processing methods for maximization of bacterial recovery

Abstract: Tissues are valuable microbiological samples that have proved superiority over swabs. Culture of tissue samples is used in the diagnosis of a variety of infections. However, as well as factors such as the site of obtaining the sample, the number of samples, and previous antibiotic use, the method of tissue processing may have an important effect on sensitivity. Data from the literature comparing different tissue processing methods is very limited. This study aimed to compare different mechanical and chemical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 20 publications
3
19
0
Order By: Relevance
“…Tissues were homogenized using the Roche magNA Lyser homogenizer (Hoffman-La Roche Ltd, Basel Switzerland) at a speed of 4500 rpm for four cycles, each lasting 45 s [18]. Prostheses were sonicated in a precision sonicator set at 50 Hz (Ultrawave Ltd, Cardiff, UK) for 5 min.…”
Section: Application Of Optimised Pma In Clinical Samplesmentioning
confidence: 99%
“…Tissues were homogenized using the Roche magNA Lyser homogenizer (Hoffman-La Roche Ltd, Basel Switzerland) at a speed of 4500 rpm for four cycles, each lasting 45 s [18]. Prostheses were sonicated in a precision sonicator set at 50 Hz (Ultrawave Ltd, Cardiff, UK) for 5 min.…”
Section: Application Of Optimised Pma In Clinical Samplesmentioning
confidence: 99%
“…There are still some issues about optimal pretreatment methods on tissues, because insufficient pretreatment might result in low bacteria yield released from tissues, while excessive pretreatment might reduce bacterial viability. Mohamed Askar reported that the use of mechanized steel ball grinding and homogenization might reduce the recovery of bacteria from tissue samples [ 6 ]. However, this study showed there were no significant effects on the viability of bacteria pretreated by various methods.…”
Section: Discussionmentioning
confidence: 99%
“…The strain of Staphylococcus aureus ( S. aureus ) ATCC 25923 (American Type Culture Collection, USA) the strain of Escherichia coli ( E. coli ) ATCC 25922 (American Type Culture Collection, USA), and the strain of Candida albicans ( C. albicans )ATCC 90029 (American Type Culture Collection, USA) were used to establish infection model in vitro. In order to simulate PJI infection as much as possible, in which pathogen may be distributed on a single surface or multiple surfaces even inside tissues [ 6 ], therefore, three tissues infection models were established (Fig. 1 ): ① Single surface infection: pipette aspirate 10 μL (200 CFU) bacterial dilution ( S. aureus /E.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A contradiction exists in using pretreatment methods, because insu cient pretreatment can result in not enough bacteria being released, and excessive pretreatment may reduce bacterial viability. Mohamed Askar reported that the use of mechanized steel ball grinding and homogenization may reduce the recovery of bacteria from tissue samples 6 . The results of this study showed that the various pretreatment methods had no signi cant effect on the viability of various bacteria.…”
Section: Discussionmentioning
confidence: 99%